Self and embodiment: A bio-phenomenological approach to dementia - Millett, Stephan (Sage, 2011)
Loss of self is widely regarded to be a consequence of dementia, and this perceived loss presents a variety of problems – not least because a clear understanding of the concept of self is elusive. This paper suggests a way to cut through problems that arise because we rely on conceptions of self in our understanding of the effects of dementia. It is proposed that we can avoid reliance on the concept of self through an approach based in bio-phenomenology. Such an approach would help us better understand the inner life of those with dementia and assist us to recognize that even in late stage dementia they are semiotic subjects with unique value